Control of Wheat Tillering by Nitrogen Availability: The Case of Strigolactones - Sigalas, Petros (2022)
Primary plant responses to nutrient-deficient conditions include changes in root and shoot architecture. Above-ground plant architecture is shaped by modulating tillering patterns. Tillering is known to be regulated by the interaction between three classes of phytohormones: auxin, cytokinins (CKs) and strigolactones (SLs). Gene expression analysis showed that nitrogen (N) limitation systematically induced the SL biosynthetic genes in the root and the basal nodes of wheat, whereas N resupply quickly reversed the induction of SL biosynthetic genes. This observation raised questions about the functionality of SLs under N-limiting conditions. Although many studies have focused on the transcriptional and hormonal changes that govern N limitation response in roots, fewer studies have focused on the molecular pathways involved in tillering modulation by N limitation during vegetative plant growth in wheat. RNA-sequencing and phytohormonal analysis in basal nodes of N-limited wheat plants showed that N limitation strongly induced bud dormancy and affected many metabolic and hormonal pathways, including changes in the expression of many N-response master regulators, strong suppression of CK biosynthesis and changes in sugar partitioning and utilization. In addition, the SL metabolic pathway was among the top enriched pathways under N limitation, implying that SLs may be involved in coordinating morphological, physiological, and transcriptional changes in response to N status. To test this hypothesis, a Tad17 SL-deficient mutant was generated using lines from the hexaploid wheat TILLING population. The phenotypic response of Tad17 mutants and transcriptomic analysis in the basal nodes showed that SLs are required but are not necessary for tiller inhibition by N limitation. SLs affected CK metabolic genes and CK levels in the basal nodes, however, the lack of SLs was not sufficient to suppress the N limitation mediated decline in CK levels, which contributed to tiller suppression under N limitation. However, lack of SL biosynthesis and imbalance in tillering regulation affected plant adaptation to N-limiting conditions. Tad17 mutant showed changes in resource allocation between root and shoot, N remobilization and the regulation of master regulators of N-response, suggesting that SLs are required for the fine-tune regulation of the N limitation transcriptional network. The genetic information and the results presented regarding the role of SLs in wheat growth and development set the foundation for and highlighted the potential of manipulation of SL metabolism in order to improve wheat architecture or nutrient use efficiency for increasing wheat crop productivity.